Implikasi Teologis Kosakata Mu’arrab dalam Al-Qur’an - Mufrodi Mufrodi; Zaki Ghufron; Nasrullah Nasrullah; Lukmanul Hakim; Nikmatullah Kusni (Alfaz (Arabic Literatures for Academic Zealots), 2022)
This study aims to explain the theological dimensions that arise due to the presence of non-Arabic vocabulary (mu'arrab) in the Qur'an. Language is a medium in conveying the intentions, needs and goals of its users, both verbally and non-verbally. Language development can follow the cultural evolution of a civilization. It is not surprising that the vocabulary of one language can be found in another language because linguistic changes occur as a result of interactions between speakers of different languages. This research is a library research, using the documentation method, namely by finding and collecting data related to the discussion in this thesis to then be analyzed using the analytical-descriptive method, namely by looking at arguments regarding non-Arabic vocabulary in Al- Qur'an from various experts, both Islamic scientists and orientalists, then the data obtained is analyzed. The aim of this research is to explore mu'arrab in terms of historical, sociocultural and linguistic aspects, and also to prove that non-Arabic vocabulary is natural as a result of the contact between languages ​​and cultures that has occurred. The results of this study indicate that there has been interaction between Arabic and northern Aramia through trade routes, migration and mixing between Aramia and Arabs in the Hijāz. With the mixing between the two languages, then there is language acculturation. Many Arabic vocabularies related to civilization and industry which are loans from Aramia is a very natural thing because it is impossible for the Arabs who are still shrouded in ignorance to recognize these vocabularies.